Evaluation of Clinical and Communication Skills of Pharmacy Students and Pharmacists with an Objective Structured Clinical Examination - Urteaga, Elizabeth M. (Am J Pharm Educ, 2015)
Objective. To evaluate how effectively pharmacy students and practicing pharmacists communicate and apply knowledge to simulations of commonly encountered patient scenarios using an objective structured clinical examination (OSCE). Design. Second-, third-, and fourth-year pharmacy students completed an OSCE as part of their required courses in 2012 and 2013. All students in both years completed identical OSCE cases. Licensed pharmacists were recruited to complete the OSCE and serve as controls in 2012. A survey assessed student perception and acceptance of the OSCE as well as student confidence in performance. Assessment. Licensed pharmacists had significantly higher clinical and communication skills scores than did pharmacy students. Student progression in communication and clinical skills improved significantly over time. Survey results indicated that students felt the OSCE was well-structured and assessed clinical skills taught in pharmacy school; 86% of students felt confident they could provide these skills. Conclusion. Objective structured clinical examinations can evaluate clinical competence and communication skills among professional students. Implementation of OSCEs may be an effective tool for assessment of the Center for the Advancement of Pharmacy Education domains.